2023
DOI: 10.1097/sla.0000000000005978
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcomes Following Endovascular Abdominal Aortic Aneurysm Repair Using Machine Learning

Abstract: Objective: To develop machine learning (ML) models that predict outcomes following endovascular aneurysm repair (EVAR) for abdominal aortic aneurysm (AAA). Summary Background Data: EVAR carries non-negligible peri-operative risks; however, there are no widely used outcome prediction tools. Methods: The National Surgical Quality Improvement Program targeted database was used to identify patients who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our work has demonstrated that ML algorithms can perform better than logistic regression and existing tools for predicting outcomes following vascular interventions. 19 , 20 , 21 , 22 , 23 In particular, we showed that procedure‐specific ML models can achieve better performance than ML algorithms developed on heterogenous surgical populations, such as the NSQIP‐based ML model by Bonde and colleagues that was trained on a pooled data set of over 2900 different surgical procedures. 19 , 20 , 21 , 22 , 23 , 24 Our vascular procedure‐specific models achieved area under the receiver operating characteristic curve (AUROC) values ≥0.90 whereas the algorithm by Bonde et al attained AUROCs between 0.85 and 0.88.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…Our work has demonstrated that ML algorithms can perform better than logistic regression and existing tools for predicting outcomes following vascular interventions. 19 , 20 , 21 , 22 , 23 In particular, we showed that procedure‐specific ML models can achieve better performance than ML algorithms developed on heterogenous surgical populations, such as the NSQIP‐based ML model by Bonde and colleagues that was trained on a pooled data set of over 2900 different surgical procedures. 19 , 20 , 21 , 22 , 23 , 24 Our vascular procedure‐specific models achieved area under the receiver operating characteristic curve (AUROC) values ≥0.90 whereas the algorithm by Bonde et al attained AUROCs between 0.85 and 0.88.…”
mentioning
confidence: 78%
“… 19 , 20 , 21 , 22 , 23 In particular, we showed that procedure‐specific ML models can achieve better performance than ML algorithms developed on heterogenous surgical populations, such as the NSQIP‐based ML model by Bonde and colleagues that was trained on a pooled data set of over 2900 different surgical procedures. 19 , 20 , 21 , 22 , 23 , 24 Our vascular procedure‐specific models achieved area under the receiver operating characteristic curve (AUROC) values ≥0.90 whereas the algorithm by Bonde et al attained AUROCs between 0.85 and 0.88. 19 , 20 , 21 , 22 , 23 , 24 Therefore, there may be value in building a ML model specifically designed to predict outcomes following lower extremity endovascular revascularization.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Using the National Surgical Quality Improvement Program targeted database, a recent study trained 6 ML models using a cohort of 16 282 patients to predict 30-day major adverse cardiovascular events after EVAR. 5 The best performing prediction model (XGBoost) achieved an area under the curve of .95 (.94-.96) and performed better compared to logistic regression [.72 (.70 - .74)]. 5 Altogether, ML-models offer new perspectives to predict complications after EVAR such as mortality, endoleak, risk of re-intervention, adverse EVAR-related events or major adverse cardiovascular events.…”
mentioning
confidence: 99%
“…5 The best performing prediction model (XGBoost) achieved an area under the curve of .95 (.94-.96) and performed better compared to logistic regression [.72 (.70 - .74)]. 5 Altogether, ML-models offer new perspectives to predict complications after EVAR such as mortality, endoleak, risk of re-intervention, adverse EVAR-related events or major adverse cardiovascular events. Such approach might help in the future to better assess the prognosis of patients, plan the intervention and optimize the follow-up of patients.…”
mentioning
confidence: 99%